THE EFFECTS OF STRENGTH-BASED PARENTING ON ADOLESCENT’S RESILIENCE AND SELF-ESTEEM IN FAMILIES USING TALENTS MAPPING - Ningrum, Diah; Supriyadi; Utami, Fitria Budi (Dialectical Literature and Educational Journal, 2022)
Today's teens face challenges more than previous generations. The use of information and technology are mentioned as among the causes of problems for teenagers in Indonesia, such as; pornography, promiscuity, premarital sex, and low motivation to study. A positive parenting is needed to help adolescents build their resilience and self-esteem to deal with obstacles in their life. Previous research on parenting styles showed that parents who used strength-based parenting helped children to develop coping skills and increased self-esteem in teenagers. Strength-based parenting is used to identify and encourage teens to recognize and use their strengths in every aspect of their life. Thus, the current study was conducted to see this parental pattern's contribution to adolescents' resilience and self-esteem. The study was held on teenagers aged 11-18 from a family using Talents Mapping in Indonesia. Sixty responses were taken by using the Strength-Based Parenting Scale, Child Youth Resilience Measure-Revised, and Rosenberg Self-Esteem Scale. Data is analysed using a regression test. The findings showed that the effects of strength-based parenting on a teenager's self-esteem are positive and significant. It was also found that resilience is positively related to youth's self-esteem. Furthermore, strength-based parenting and resilience are simultaneously positive and significant on teenagers' self-esteem, as 10.4%.